Blockchain for Economic Diversification: Measuring Public investment and Financial Sector Innovation in the GCC - Sadraoui, Tarek; Mili, Hela; Alharaib, Mansour (Journal of Posthumanism, 2025)
The GCC economies have taken strategic initiatives to incorporate blockchain technology to introduce more innovation in finance and to reduce their dependence on oil. This paper presents the empirical analysis of the impact of blockchain implementation on economic diversification in six GCC countries from 2010 to 2024. The main objective of this paper is to analyze how institutional quality. along with financial development and technology innovation. interacts in affecting diversification outcomes. Panel data econometric techniques are conducted. including Fixed Effects. Pooled Mean Group estimation. and System GMM estimation. to assess blockchain innovation. FinTech maturity. government-driven digital innovation. and oil dependence for their impacts on the measures of diversification. The findings indicate that blockchain adoption and FinTech expansion have a substantial long-run positive impact on economic diversification. even as oil dependency remains a major structural constraint. On the other hand. innovation of government has a slightly positive impact on the process of diversification. while foreign direct investment is statistically insignificant. Since the evidence suggests that improvements in diversification are caused by. rather than occurring concurrently with. digital technologies. robustness tests confirm the diagnostic and causality tests. These findings show that the GCC is increasingly capable of leveraging digital transformation in the pursuit of strong post-oil economies. enabled in great measure by blockchain finance and governance. The policy implications emphasize the importance of legislative harmonization. investments in blockchain infrastructure and education. and continued public-private partnerships in the consolidation of the long-term benefits of decentralized innovation.